Analysis of Critical Thinking Skills in Fifth Grade Elementary School Students on Fractions - Sarah Fazilla; Fauziana; Hasmanovi (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
Mathematics and critical thinking skills are two things that cannot be separated, because mathematics is understood through critical thinking and vice versa. Critical thinking is trained through studying mathematics. Critical thinking can help students improve their understanding of the material being studied by evaluating it critically. It can be used by students to solve problems and as a consideration in making correct decisions in learning mathematics. However, at SD Negeri 1 it is clear that there are still many students who are unable to solve mathematical problems because of the students' low critical thinking skills. The aim of this research is to find out how students' critical thinking abilities are and what the teacher's role is in improving students' critical thinking abilities. The method used is descriptive qualitative with data analysis techniques using data reduction. The data sources in this research are primary and secondary data. data obtained from interview techniques and documentation. The results of the research show that students who are classified as having high critical thinking abilities are students who are able to fulfill all critical thinking indicators, students who have moderate critical thinking abilities are able to fulfill the indicators of interpretation, analysis and evaluation, students who have low critical thinking abilities are unable to interpret problems and are unable to fulfill the indicators of analysis, evaluation and inference. Therefore, teachers play a very important role in improving students' critical thinking abilities and training students to develop thinking abilities by providing practice questions to students so that they can help students improve their critical thinking abilities.